The role of exercise-induced myokines in promoting angiogenesis - Qi, Chao; Song, Xianjing; Wang, He; Yan, Youyou; Liu, Bin (Frontiers in Physiology, 2022)
Ischemic diseases are a major cause of death or disability in the clinic. Operation or drug treatment often has poor effect on patients with tissue and organ ischemia caused by diffuse stenoses. Promoting angiogenesis is undoubtedly an effective method to improve perfusion in ischemic tissues and organs. Although many animal or clinical studies tried to use stem cell transplantation, gene therapy, or cytokines to promote angiogenesis, these methods could not be widely applied in the clinic due to their inconsistent experimental results. However, exercise rehabilitation has been written into many authoritative guidelines in the treatment of ischemic diseases. The function of exercise in promoting angiogenesis relies on the regulation of blood glucose and lipids, as well as cytokines that secreted by skeletal muscle, which are termed as myokines, during exercise. Myokines, such as interleukin-6 (IL-6), chemokine ligand (CXCL) family proteins, irisin, follistatin-like protein 1 (FSTL1), and insulin-like growth factor-1 (IGF-1), have been found to be closely related to the expression and function of angiogenesis-related factors and angiogenesis in both animal and clinical experiments, suggesting that myokines may become a new molecular target to promote angiogenesis and treat ischemic diseases. The aim of this review is to show current research progress regarding the mechanism how exercise regulates myokine expression and how myokines promote angiogenesis. In addition, the therapeutic potential of myokines in angiogenesis are also discussed to provide theoretical basis for the development of new strategies for treating ischemic diseases in the future.